2018
DOI: 10.1016/j.scitotenv.2018.01.337
|View full text |Cite
|
Sign up to set email alerts
|

Sorption, plant uptake and metabolism of benzodiazepines

Abstract: Reuse of treated wastewater for irrigation of crops is growing in arid and semi-arid regions, whilst increasing amounts of biosolids are being applied to fields to improve agricultural outputs. Due to incomplete removal in the wastewater treatment processes, pharmaceuticals present in treated wastewater and biosolids can contaminate soil systems. Benzodiazepines are a widely used class of pharmaceuticals that are released following wastewater treatment. Benzodiazepines are represented by a class of compounds w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 44 publications
1
28
0
Order By: Relevance
“…Our results were in agreement with recent findings in Carter et al (2018), in which they observed the formation of nordiazepam, temazepam and oxazepam in radish and silverbeet plants exposed to diazepam and chlordiazepoxide. They similarly showed nordiazepam to be the major metabolite with oxazepam and temazepam constituting a much smaller fraction at the end of 28 d cultivation in soil.…”
Section: Metabolism Of Diazepam In Cucumber and Radish Seedlingssupporting
confidence: 94%
“…Our results were in agreement with recent findings in Carter et al (2018), in which they observed the formation of nordiazepam, temazepam and oxazepam in radish and silverbeet plants exposed to diazepam and chlordiazepoxide. They similarly showed nordiazepam to be the major metabolite with oxazepam and temazepam constituting a much smaller fraction at the end of 28 d cultivation in soil.…”
Section: Metabolism Of Diazepam In Cucumber and Radish Seedlingssupporting
confidence: 94%
“…Therefore, BCFs calculated on the basis of pharmaceutical concentration in bulk soil are not comparable among the studies using different soils because of the varying affinities of pharmaceuticals to soils. For instance, soil-based BCFs of seven benzodiazepines in radish could vary by up to 86.0 times between two soils (Carter et al, 2018). The difference of soil-based BCFs between three soils for caffeine, carbamazepine, and lamotrigine in tomato or cucumber can up to 20.0, 7.8, and 245 times, respectively (Goldstein et al, 2014).…”
Section: Takedownmentioning
confidence: 99%
“…Wu et al (2015) studied the fate of pharmaceuticals and personal care products added to soil irrigated with treated wastewater or biosolid-amended soil. Carter et al (2018) studied the sorption, plant uptake, and metabolism of benzodiazepines, a widely used class of pharmaceuticals that are recalcitrant to wastewater treatment. According to the authors, the mechanisms involved in pharmaceutical uptake and transport in plants are very complex.…”
Section: Resultsmentioning
confidence: 99%